Two New Taxa of Goniasteridae (Asteroidea, Echinodermata) and Noteworthy Observations of Deep-Sea Asteroidea by the NOAA Ship Okeanos Explorer in the North and Tropical Atlantic - Mah, Christopher L. (Zootaxa, 2024)
Two new species and one new genus, collected by NOAA ship Okeanos Explorer, Bathyceramaster kelliottae n. sp. and Rhianastra isosceles n. gen., n. sp. (Goniasteridae; Asteroidea) are described from deep-sea settings in the North Atlantic. Two potentially undescribed species are observed from imagery and new in situ observations further elucidate life modes and feeding behavior of several species from North Atlantic deep-sea habitats. New occurrences of Atlantic Neomorphaster are presented and Neomorphaster forcipatus is synonymized with Neomorphaster margaritaceus.